Brown spot - A new disease of vanilla (Vanilla planifolia Andrews) from India - M Anandaraj, R S Bhai, (Journal of Spices and Aromatic Crops, 2006)
A new disease characterized by the appearance of small water-soaked spots which laterdeveloped into characteristic brownish sunken lesions on vanilla beans (Vanilla planifolia)was noticed during September 2004 in Kozhikode District (Kerala) where vanilla is grownas an intercrop with coconut, arecanut and clove. Studies on the causal organism and patho-genicity tests showed that the disease is caused by the fungus Cylindrocladium quinqueseptatum.